The evolution of tractorization in India’s low-wage economy: Key patterns and implications - Bhattarai, Madhusudan; Joshi, Pramod Kumar; Shekhawa, R. S.; Takeshima, Hiroyuki (International Food Policy Research Institute, 2017)
This study reviews the evolution of tractor use in India in the past few decades, and supplements this with a panel model analysis using factors associated with state-level tractor density growth. Growth in tractor use in India, unlike that in the United States and Japan, has occurred at relatively low wage rates and with a substantial majority of the workforce remaining in the agricultural sector. Considerable growth in domestic manufacturing has contributed to growth in tractor densities. Tractor density across the 14 major states in India between 1982 and 2012 was positively affected by income per capita, cropping intensity, and the average size of farmland holdings. Tractor intensity grew at a fast pace even in low-wage regions of India, indicating that relatively lower labor wages might not have been a binding factor for diffusion of farm machinery and tractors among smallholding farmers in India.